Impact of energy availability, health, and sex on hemoglobin-mass responses following live-high-train-high altitude training in elite female and male distance athletes - Heikura, I. A.; Burke, L. M.; Bergland, D.; Uusitalo, A. L. T.; Mero, A. A.; Stellingwerff, T. (International Journal of Sports Physiology and Performance, 2018)
Purpose: The authors investigated the effects of sex, energy availability (EA), and health status on the change in hemoglobin mass (DeltaHbmass) in elite endurance athletes over ~3-4 wk of live-high-train-high altitude training in Flagstaff, AZ (2135 m; n=27 women; n=21 men; 27% 2016 Olympians). Methods: Precamp and postcamp Hbmass (optimized carbon monoxide rebreathing method) and iron status were measured, EA was estimated via food and training logs, and a Low Energy Availability in Females Questionnaire (LEAFQ) and a general injury/illness questionnaire were completed. Hypoxic exposure (h) was calculated with low (<500 h), moderate (500-600 h), and high (>600 h) groupings. Results: Absolute and relative percentage ?Hbmass was significantly greater in women (6.2% [4.0%], P<.001) than men (3.2% [3.3%], P=.008). %?Hbmass showed a dose-response with hypoxic exposure (3.1% [3.8%] vs 4.9% [3.8%] vs 6.8% [3.7%], P=.013). Hbmasspre was significantly higher in eumenorrheic vs amenorrheic women (12.2 [1.0] vs 11.3 [0.5] g/kg, P=.004). Although statistically underpowered, %?Hbmass was significantly less in sick (n=4, -0.5% [0.4%]) vs healthy (n=44, 5.4% [3.8%], P<.001) athletes. There were no significant correlations between self-reported iron intake, sex hormones, or EA on Hbmass outcomes. However, there was a trend for a negative correlation between LEAFQ score and %DeltaHbmass (r=-.353, P=.07). Conclusions: The findings confirm the importance of baseline Hbmass and exposure to hypoxia on increases in Hbmass during altitude training, while emphasizing the importance of athlete health and indices of EA on an optimal baseline Hbmass and hematological response to hypoxia.